Sexual Orientation Disparities in Cardiovascular Biomarkers Among Young Adults - Hatzenbuehler, Mark L.; McLaughlin, Katie A.; Slopen, Natalie (American journal of preventive medicine, 2013)
Emerging evidence from general population studies suggests that lesbian, gay, and bisexual (LGB) adults are more likely to experience adverse cardiovascular outcomes relative to heterosexuals. No studies have examined whether sexual orientation disparities exist in biomarkers of early cardiovascular disease risk. To determine whether sexual orientation disparities in biomarkers of early cardiovascular risk are present among young adults. Data come from Wave IV (2008–2009) of the National Longitudinal Study for Adolescent Health (N=12,451), a prospective nationally representative study of U.S. adolescents followed into young adulthood (mean age=28.9 years). A total of 520 respondents identified as lesbian, gay, or bisexual. Biomarkers included C-reactive protein, glycosylated hemoglobin, systolic and diastolic blood pressure, and pulse rate. Analyses were conducted in 2012. In gender-stratified models adjusted for demographics (age, race/ethnicity); SES (income, education); health behaviors (smoking, regular physical activity, alcohol consumption); and BMI, gay and bisexual men had significant elevations in C-reactive protein, diastolic blood pressure, and pulse rate, compared to heterosexual men. Despite having more risk factors for cardiovascular disease, including smoking, heavy alcohol consumption, and higher BMI, lesbians and bisexual women had lower levels of C-reactive protein than heterosexual women in fully adjusted models. Evidence was found for sexual orientation disparities in biomarkers of cardiovascular risk among young adults, particularly in gay and bisexual men. These findings, if confirmed in other studies, suggest that disruptions in core physiologic processes that ultimately confer risk for cardiovascular disease may occur early in the life course for sexual-minority men.